Endovascular Treatment of Symptomatic Radiation-Induced Basilar Artery Stenosis 25 Years after Medulloblastoma - Gölitz, P.; Knossalla, F.; Ott, S.; Struffert, T.; Doerfler, A. (Neuropediatrics, 2011)
Intracranial stenosis as late sequela after cerebral radiation therapy for medulloblastoma is an exceptionally rare finding. We report for the first time a case of 31-year-old patient with a history of medulloblastoma 25 years ago and now presenting with radiation-induced high-grade basilar stenosis and recurrent ischemic symptoms despite best medical therapy. The stenosis was treated successfully with angioplasty followed by stenting using a self-expandable microstent. Additionally, MRI revealed multiple cavernomas, illustrating that radiation-induced microbleeds may occur.
Keywords: radiation-induced intracranial vessel stenosis; endovascular treatment; parenchymal involvement; flat detector computed tomography (FD-CT)